Low but significant genetic differentiation underlies biologically meaningful phenotypic divergence in a large Atlantic salmon population. Issue 20 (12th October 2015) - Aykanat, Tutku; Johnston, Susan E.; Orell, Panu; Niemelä, Eero; Erkinaro, Jaakko; Primmer, Craig R.
Abstract Despite decades of research assessing the genetic structure of natural populations, the biological meaning of low yet significant genetic divergence often remains unclear due to a lack of associated phenotypic and ecological information. At the same time, structured populations with low genetic divergence and overlapping boundaries can potentially provide excellent models to study adaptation and reproductive isolation in cases where high‐resolution genetic markers and relevant phenotypic and life history information are available. Here, we combined single nucleotide polymorphism (SNP)‐based population inference with extensive phenotypic and life history data to identify potential biological mechanisms driving fine‐scale subpopulation differentiation in Atlantic salmon (Salmo salar) from the Teno River, a major salmon river in Europe. Two sympatrically occurring subpopulations had low but significant genetic differentiation (FST = 0.018) and displayed marked differences in the distribution of life history strategies, including variation in juvenile growth rate, age at maturity and size within age classes. Large, late‐maturing individuals were virtually absent from one of the two subpopulations, and there were significant differences in juvenile growth rates and size at age after oceanic migration between individuals in the respective subpopulations. Our findings suggest that different evolutionary processes affect each subpopulation and that hybridization and subsequent selection may maintain low genetic differentiation without hindering adaptive divergence.